Aligning stakeholders' mental models on carsharing system using remote focus group method. (December 2021) - Jittrapirom, Peraphan; Boonsiripant, Saroch; Phamornmongkhonchai, Monthira
Abstract: The novelties of new mobility solutions, such as carsharing, may instill different expectations and understanding of the concepts among stakeholders. These differences in their 'mental models' can hamper the wider implementation of the concept and delay a transition toward a more sustainable transport system. In this study, we implemented a participatory group modeling building approach (GMB) to explore the differences and to integrate the mental models of stakeholders concerning the carsharing operation in Bangkok, Thailand. Through the process, we identified apparent differences in how participants visioned a successful carsharing operation and created an initial shared understanding in the form of a causal loop diagram. The qualitative model included attributes influencing the success of carsharing and possible policy interventions. The results illustrated the effectiveness of GMB as a participatory approach for transport planning.